Profile Of Maximum Volume Level Of Takraw Athlete State High School Of Sports Ability (SMANKO) Bengkulu Province - Feby Elra Perdima; Suwarni Suwarni (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the maximum oxygen uptake of athletesSepak takrawSports Talent State High School (SMANKO) Bengkulu Province. This study is a descriptive study. Collect data using a survey method with tests and measurements. This instrument is used to measure the maximum VO2 test using the Bleep test. The subject of this research is AthleteSepak takrawThe State High School of Sports Talent (SMANKO) of Bengkulu Province totaled 11 athletes. The data analysis technique used in this research is quantitative description analysis presented in percentage form. The conclusion that can be drawn is that the athletes' maximum oxygen uptake is as follows: In the very good category there are 0 athletes (0%), in the good category there are 0 athletes (0%), the moderate category there are 11 athletes (100%), in the poor category there are 0 athletes (0%) and very bad category there are 0 athletes (0%)